2021
DOI: 10.3390/app11157055
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining Associated with Analysis of Structure, Antioxidant Activity Reveals the Potential Production of Levan-Rich Exopolysaccharides by Food-Derived Bacillus velezensis VTX20

Abstract: Exopolysaccharides (EPSs) produced by Bacillus species have recently emerged as promising commercial antioxidants in various industries, such as pharmaceutics and biomedicine. However, little is known about EPS production and function from Bacillus velezensis so far. In the present study, the effect of sugar sources on EPS production by B. velezensis VTX20 and the genetic biosynthesis, characteristics, and antioxidant activity of the resulting EPS were evaluated. The strain VTX20 produced the maximum EPS yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…The hydroxyl radical is one of the most reactive free radicals in a biological system [ 84 ]. This is a type of free radical with the most active chemical properties and that can cause the most harm in comparison to other free radicals, as it damages DNA base sequences [ 85 ]. The scavenging activity of the hydroxyl radical is commonly used to evaluate the ability of compounds to scavenge free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyl radical is one of the most reactive free radicals in a biological system [ 84 ]. This is a type of free radical with the most active chemical properties and that can cause the most harm in comparison to other free radicals, as it damages DNA base sequences [ 85 ]. The scavenging activity of the hydroxyl radical is commonly used to evaluate the ability of compounds to scavenge free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…They are two strains of gram‐positive bacteria known for their exopolysaccharides production capacity (Ansorena & Astiasarán, 2016; Nguyen et al, 2021) which are the main component of EPSs (Costa et al, 2018). For gram‐negative bacteria, although no study reported an increase in EPS synthesis under environmental stresses, it was demonstrated that there are functional exopolysaccharide genes (Whitney & Howell, 2013; Zeidan et al, 2017) which are also regulated expression by environmental conditions (Vu et al, 2021; Wen & Zhang, 2015). This demonstrates the possibility of applying environmental stresses to the self‐encapsulation of different probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl radical scavenging activity. The hydroxyl radical scavenging activity of SX6 extract was evaluated with slight modifications (Liu et al 2009;Vu et al 2021). About 1.0 ml of 70% ethanol extract was added to the mixture containing 1.0 ml of 0.75 mM 1,10-phenanthroline, 1.0 ml of 0.75 mM FeSO 4 , 1.0 ml of 0.01% H 2 O 2 , and 1.5 ml of 0.15 M sodium phosphate buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…DPPH-radical scavenging activity. The 2-diphenyl-1-picrylhydrazyl (DPPH) assay was carried out as in the previous studies (Kadaikunnan et al 2015;Vu et al 2021). The crude extract dissolved in 70% ethanol was reacted with 0.2 ml of 0.1 mM 2,2-diphenyl-1-picrylhydrazyl (DPPH) followed by 2.0 ml of deionized water.…”
Section: Methodsmentioning
confidence: 99%